2016
DOI: 10.3389/fpsyg.2016.01497
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery Patients' Perceptions of Weight-Related Stigma in Healthcare Settings Impair Post-surgery Dietary Adherence

Abstract: Background: Weight-related stigma is reported frequently by higher body-weight patients in healthcare settings. Bariatric surgery triggers profound weight loss. This weight loss may therefore alleviate patients' experiences of weight-related stigma within healthcare settings. In non-clinical settings, weight-related stigma is associated with weight-inducing eating patterns. Dietary adherence is a major challenge after bariatric surgery.Objectives: (1) Evaluate the relationship between weight-related stigma and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 90 publications
4
85
0
Order By: Relevance
“…Across these measures, studies have demonstrated significant correlations between WBI and dietary restraint ( r values = 0.21–0.50), eating concerns ( r values = 0.37–0.64), drive for thinness ( r = 0.47) and measures assessing disinhibition, uncontrolled eating and emotional eating ( r values = 0.46–0.65). Moderate to strong correlations ( r values = 0.29–0.77) were documented for associations between WBI and global or total scores for measures of disordered eating . As with binge eating, measures of eating pathology were associated with WBI in both clinical and community samples and across body weight statuses.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Across these measures, studies have demonstrated significant correlations between WBI and dietary restraint ( r values = 0.21–0.50), eating concerns ( r values = 0.37–0.64), drive for thinness ( r = 0.47) and measures assessing disinhibition, uncontrolled eating and emotional eating ( r values = 0.46–0.65). Moderate to strong correlations ( r values = 0.29–0.77) were documented for associations between WBI and global or total scores for measures of disordered eating . As with binge eating, measures of eating pathology were associated with WBI in both clinical and community samples and across body weight statuses.…”
Section: Resultsmentioning
confidence: 94%
“…normal weight, overweight and obesity). Among samples that only included persons with overweight/obesity, 16 studies found significant associations between WBI and BMI or weight status , and 17 found no significant associations . In studies that found significant associations, r values ranged from 0.12 to 0.40.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, a medical diagnosis can act to help people to cope with their weight concerns by reducing their internalized stigma or the belief that their problems are self‐inflicted and shameful. Such internalized stigma is itself a barrier to effective weight loss and may impair weight loss maintenance .…”
Section: Supporting Treatmentmentioning
confidence: 99%
“…Brolin et al 20 reported only one‐third of patients adhered to supplements at 10 years while 8% never took supplements at all. Raves et al 21 surveyed postoperative bariatric patients to measure experiences of weight‐related stigma and demonstrated that internalized stigma and general experiences of weight‐related stigma predicted worse dietary adherence, even after weight loss. Spadola et al 22 reported alcohol abuse was present in 21% of young adults before bariatric surgery (and was a risk factor for increased alcohol use after bariatric surgery) while 4.2% developed alcohol abuse after bariatric surgery.…”
Section: What Are the Presurgical And Postsurgical Variables And Mechmentioning
confidence: 99%